Analyze the Win-Win Problem between Enterprises and Society in The Exercise of Corporate Social Responsibility - Yang, Yishu (Transactions on Economics, Business and Management Research, 2024)
This study examines the corporate social responsibility (CSR) activities implemented by Rhino Africa Safaris (RA), particularly with the protection of endangered animals. In response to escalating worldwide environmental concerns, RA has adopted innovative tactics to promote conservation initiatives and strengthen its corporate identity. This article seeks to examine effective strategies for executing CSR that advantage both society and enterprises. The study employs qualitative analysis to apply stakeholder theory and shared value theory in the context of RA’s CSR initiatives. The findings indicate that RA’s CSR strategy is effective as it fosters enduring partnerships with stakeholders, facilitates resource integration, enhances customer loyalty and brand perception through proactive measures, and employs a distinctive customer engagement model that elevates public awareness and support for conservation initiatives. Recommendations advocate for the enhancement of collaborative initiatives with stakeholders, the amplification of community engagement in CSR projects, and the advancement of innovative techniques for customer interaction. This study emphasizes the need to integrate CSR into business models to foster sustainable development, offering valuable insights for other companies aiming to enhance their social impact while achieving economic success.